Discursive Power in the Hybrid Media System: The Case of Chinese Neologisms - Nancy Liu (Media and Intercultural Communication: A Multidisciplinary Journal)
Discursive power is conventionally conceptualized as the power of those in control over others. This study approaches this subject from a novel perspective by proposing that such power is inherent within neologisms or Internet buzzwords in the hybrid media system. This power is rampant and omnipotent, and is exercised voluntarily by some actors to accommodate to the mass media market’s demand for novelty or appeal. Situated within the framework of media systems, this qualitative discourse analysis study was conducted on the data collected from multiple sources from 2019 to 2021. It was found that indicators of the discursive power are not just embodied in the topics, frames and speakers, but also manifested in the trends, contexts and sources of news reports. This study will contribute to knowledge by proposing that the usage patterns of neologisms characterizes the strategies deployed in both the state media and the social media for attention and power in the communication space.